Autores (2015)
Este documento contiene en texto completo el articulo Autores publicado en Desafíos; Vol. 27, Núm. 2 (2015): (julio-diciembre) El mundo interno y la política; 331-335;2145-5112;0124-4035;10.12804/desafios27.2.2015